Waste management education for the community of Duri Kepa Village, West Jakarta - Aprilita Rina Yanti Eff; Mellisa Resmiati; Mayang Ayu Purborini; Devi Angeliana Kusumaningtiar (Universitas Muhammadiyah Magelang, 2023)
The RW. 02 in Duri Kepa Village, Kebon Jeruk District, West Jakarta, is a densely populated region situated close to the market, where frequent floods occur. The market area is marred by indiscriminate rubbish disposal, and it has been used as a temporary landfill, leading to a buildup of waste, unpleasant odors, and triggering floods. Community service activities aim to enhance residents' awareness and knowledge of waste management. These activities involve outreach and education conducted for RW residents in Duri Kepa Village. Posters and brochures are distributed from house to house, complemented by lectures and discussions. Analysis of pre-test and post-test results on 70 participants reveals that the socialization and education efforts successfully increased knowledge about waste management by 24.99 points.